NAC Transcription Factor TwNAC01 Positively Regulates Drought Stress Responses in Arabidopsis and Triticale - Wang, Meng; Ren, Li-Tong; Wei, Xiao-Yong; Ling, Yue-Ming; Gu, Hai-Tao; Wang, Shan-Shan; Ma, Xue-Feng; Kong, Guang-Chao (Frontiers in Plant Science, 2022)
The NAC transcription factors play important roles in regulating plant growth, development, and senescence, and responding to biotic and abiotic stressors in plants. A novel coding sequence (1059 bp) was cloned from hexaploid triticale in this study. The putative protein (352 amino acids) encoded by this sequence was over 95% similar to the amino acid sequence of a NAC protein from Aegilopsis tauschii (XP020161331), and it formed a clade with Ae. tauschii, durum wheat, and barley. The putative protein contained a conserved nature actomyosin (NAM) domain (129 consecutive amino acids) between the 20th and 148th amino acids at the N-terminus and three transcription activation regions at the C-terminus. The novel gene was identified as a triticale NAC gene localized in the nucleus and designated as TwNAC01 (GenBank accession MG736919). The expression levels of TwNAC01 were the highest in roots, followed by leaves and stems when triticale lines were exposed to drought, polyethylene glycol 6000 (PEG6000), NaCl, cold, methyl jasmonate (MeJA), and abscisic acid (ABA). Transgenic Arabidopsis thaliana overexpressing TwNAC01 had significantly lower leaf water loss rates and longer roots than wild-type (WT) A. thaliana. Virus-induced silencing of the TwNAC01 gene in triticale delayed root development and decreased length of primary root. Under drought stress, leaves of TwNAC01-silenced triticale had higher levels of malondialdehyde (MDA) and hydrogen peroxide (H2O2), but lower relative water content (RWC), net photosynthetic rate, stomatal conductance, intercellular CO2 concentration, and transpiration rate than the leaves of the WT. Gene overexpression and silencing experiments suggested that TwNAC01 improves plant stress tolerance by increasing root length, regulating the water content of plant leaves by reducing MDA and H2O2 content, and adjusting respiration rate. The results suggest that TwNAC01 is a novel NAC transcription factor gene that can be exploited for triticale and cereal improvement.